As plantas e seus usos na "Guiné do Cabo Verde" : Almada, Donelha e Lemos Coelho (séculos XV-XVII) - Jahnke, Teane Mundstock (2017)
This dissertation researches the uses of plants among the African, Luso-african and Portuguese populations in the region called "Guinean of Cape Verde" and the social, religious, commercial and political relations involved in these processes, from the XVth to the XVIIth centuries. We studied the works of André Alvares de Almada, the "Tratado Breve dos Rios da Guiné do Cabe Verde, dês do Rio de Sanagá até os baixos de Santa Ana de todas as nações de negros que há na dita costa e de seus costumes, armas, trajos, juramentos, guerras” of 1594, as the principal historiographical source, and also the works of André Donelha, " Descrição da Serra Leoa e dos Rios de guiné do cabo verde”, 1625 and Francisco Lemos Coelho, “Descrição da costa da Guine desde o Cabo Verde athe Serra Lioa com todas as ilhas e rios que os brancos navegam”, of 1669; e “Discripção da Costa de Guiné, e situação de todos os portos e rios della, e roteyro para se poderem navegar todos seus rios”, of 1684. The concept "Guinea of Cape Verde" acquired official character for the Portuguese Kingdom and defined the region of the Atlantic African coast between the Senegal river and the south of present-day Sierra Leone on the border of Guine Conakry. The work presents the historical context of the sources, participant in the specific Guinea of Cape Verde’s commercial and cultural relations. As the human being is considered an active agent and a subject of the nature, we argued that the exchanges, appropriations and circulation of knowledge related to the flora are multilateral. It was analyzed how the plants take part in the commercial, productive and environmental relations of the region and the way in which the authors present their uses and specificities, using examples such as rice, kola nut and cotton. Lastly, we seek to understand how the flora partakes of social, political and religious relations in the region, and how this knowledge circulates among African, Portuguese-African and Portuguese diverse populations, generating new ways of interpreting the natural world.